PERKEMBANGAN KEMAHIRAN BERBAHASA PADA ANAK - Irianto NFN (Balai Bahasa Provinsi Papua, 2019)
Language device is the important part in early human life. Some perspectives were done depth about children language development. This paper will express about children language device, because we was born with language potencies, it is the language tools. That development is complex, not only about the fact and reality that were represented by sounds. But, go far from language limits that were developed on child as a reflex, without the effort and formally instruction that made their use language were understood by the other. Its developing was influenced by natural factor versus structural factor. In determined part, language is the result from tool of the language skill and the other part it is result of experience process. Language skill was influenced by commonly versus specify, when most of psychologist convinced if language has some special things on it.